DESAIN KOTAK PENGHANGAT MAKANAN DENGAN MEMANFAATKAN GAS BUANG SEPEDA MOTOR - Fadly Ahmad Kurniawan Nasution; Muhammad Arifin (Jurnal Simetri Rekayasa, 2021)
A warming box is a box that can store food and warm food on delivery services and can keep food warm until it reaches consumers. The system in this food heating box uses the principle of pipe heat to deliver heat coming from motorcycle exhaust gases to the food storage box on the delivery service. In the design of the food warming box, there are several layers in the box, including a layer of stainless stell plate, cocopeat insulator layer, aluminum layer, fiber layer. This food warming box has dimensions of 400 mm× 400 mm× 465 mm, from the design obtained the result of the design of the storage box in the form of the inner surface area of the storage box of 3832.9 〖cm〗^2 at each level. In this food warmer box, a heat exchanger is also used as a heat transfer device and has dimensions of 400 mm× 300 mm×100 mm.